1998
DOI: 10.1159/000006827
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis, Myocyte Degeneration and Heart Failure in Chronic Experimental Aortic Regurgitation

Abstract: Myocardial fibrosis and myocyte degeneration have been reported in patients with chronic aortic regurgitation (AR), and may be related to the pathophysiology of congestive heart failure (CHF) in this disease. To define the relationship between myocardial histopathologic variations and CHF in chronic AR, we performed gross and microscopic evaluations of postmortem tissue from a rabbit model of chronic AR manifesting left ventricular (LV) responses to AR similar to those in humans. Moderate-to-severe chronic AR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 40 publications
3
29
0
4
Order By: Relevance
“…Our results in cultured AR fibroblasts, plus earlier findings of histologically evident fibrosis in the absence of CHF 4 and, occasionally, in the absence of apparent myocyte damage, suggest that myocardial fibrosis in AR may be, at least in part, a primary response to volume overload. This is supported by our finding of similar cellular/molecular abnormalities in cultured AR fibroblasts and in normal fibroblasts subjected for several days (beyond the time of immediate gene expression changes) to dynamic, cyclical strain modeling that of AR.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Our results in cultured AR fibroblasts, plus earlier findings of histologically evident fibrosis in the absence of CHF 4 and, occasionally, in the absence of apparent myocyte damage, suggest that myocardial fibrosis in AR may be, at least in part, a primary response to volume overload. This is supported by our finding of similar cellular/molecular abnormalities in cultured AR fibroblasts and in normal fibroblasts subjected for several days (beyond the time of immediate gene expression changes) to dynamic, cyclical strain modeling that of AR.…”
Section: Discussionsupporting
confidence: 76%
“…This is consistent with our earlier report of histologically evident fibrosis in experimental animals with chronic AR. 4,5 In these animals, myocardial collagen content was normal despite exuberant fibrosis in some animals; noncollagen ECM proteins were not assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cardiac fibrosis is a well known cause of altered contractility of the myocardium (30,31), left-ventricular contractility appears to be adequately maintained at this stage, as seen from the finding that FS of the cardiac muscle did not differ between the LPD and NPD offspring. It appears likely that the left-ventricular hypertrophy observed in the IUGR offspring leads to encroachment on the left ventricle chamber size during systole, as judged from the significant decrease in end-systolic dimensions in the hearts of IUGR animals.…”
Section: Altered Cardiac Growth In Offspring With Iugrmentioning
confidence: 97%
“…For cases with chronic AR, histological study has demonstrated that LV fibrosis and myocyte necrosis were in proportion to the hemodynamic burden in rabbit model even in early period. 10 In another study, AR-induced myocardial damage was demonstrated to occur even before functional deterioration.…”
Section: Discussionmentioning
confidence: 94%